2012
DOI: 10.1007/s10447-012-9153-9
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of Acculturation, Enculturation, and Ethnic Identity: Influence of Psychocultural Constructs on Conscientiousness and Expectations of Higher Education Among Latinos

Abstract: This study investigated the influence of psychocultural variables (e.g., acculturation, enculturation, ethnic identity) and personality characteristics in relation to educational expectations among 345 Latino middle school students in the U.S. Results from a path model indicate that 24.4 % of the variance of educational expectations was accounted for by all predictor variables included in the model. Age, acculturation, and conscientiousness had statistically significant direct effects on educational expectatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
16
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 33 publications
0
16
0
Order By: Relevance
“…For the purposes of this article, acculturation will refer to Latino/as' adaptation to Anglo American culture, while enculturation will describe students' orientation toward Latino/a culture. Since most postsecondary institutions and American work environments are influenced and based primarily on Anglo culture, Latino/as with the ability to navigate mainstream culture while maintaining their cultural roots may possess additional skills that assist in their educational and career development (e.g., Cano et al, 2012). In other words, Latino/as, who are familiar with both Anglo and Hispanic cultures and who have knowledge of cultural attitudes, values, and beliefs from both cultures, may be more comfortable in the college environment and have greater expectations of occupational opportunities.…”
Section: Acculturation and Enculturationmentioning
confidence: 99%
“…For the purposes of this article, acculturation will refer to Latino/as' adaptation to Anglo American culture, while enculturation will describe students' orientation toward Latino/a culture. Since most postsecondary institutions and American work environments are influenced and based primarily on Anglo culture, Latino/as with the ability to navigate mainstream culture while maintaining their cultural roots may possess additional skills that assist in their educational and career development (e.g., Cano et al, 2012). In other words, Latino/as, who are familiar with both Anglo and Hispanic cultures and who have knowledge of cultural attitudes, values, and beliefs from both cultures, may be more comfortable in the college environment and have greater expectations of occupational opportunities.…”
Section: Acculturation and Enculturationmentioning
confidence: 99%
“…Y. Flores et al (2006) found that heritage-culture retention was not associated with educational goals. Similarly, a study of Latinx middle school students found that while receiving-culture acquisition was a significant predictor of educational outcomes, heritage-culture retention was not (Cano et al, 2012). Conversely, a study of Mexican American college students found that heritage-culture retention was significantly associated with academic persistence (Ojeda, Castillo, Meza, & Piña-Watson, 2014).…”
Section: Psychocultural and Sociocultural Factorsmentioning
confidence: 99%
“…account for these positive relationships-such as increased self-esteem (e.g., Schwartz et al, 2007) and conscientiousness (e.g., Cano et al, 2012)-have also been described. As a whole, this body of research supports a positive relation between Latina/o ethnic identity and a variety of academic outcomes and has begun to clarify some of the mechanisms that drive this relation.…”
mentioning
confidence: 98%
“…For instance, researchers have found that involvement in European American culture-but not Latina/o cultures-is positively related to the educational persistence and college application rates of Mexican American high school seniors (e.g., Castillo et al, 2010). Among Latina/o middle school students, involvement in European American culture is positively associated with higher educational expectations while involvement in Latina/o cultures predicts lower educational expectations (Cano et al, 2012). As a whole, the available research suggests that academic variables tend to be positively related to involvement in European American culture and negatively-or non-significantly-to involvement in Latina/o cultures.…”
mentioning
confidence: 99%